(untitled) (Research, Society and Development, 2020)
Objective: To identify measures to prevent urinary tract infection associated with the use of indwelling bladder catheters, through health education. Method: Descriptive, quantitative research with 95 nursing professionals from a public hospital in the city of Rio de Janeiro. Data production took place from July to September 2019, using the instrument “Risk screening for urinary tract infection associated with the use of an indwelling bladder catheter”, containing closed questions and a game of errors, anchored in gamification. Analysis was carried out using absolute, relative values and accumulated frequency, in the light of the theoretical framework. Results: The daily frequency of urethral meatus hygiene was erroneously pointed out by 44.21% of the participants. The conduct to be taken in case of disconnection of the closed drainage system with the indwelling bladder catheter was asserted by 87.37% of the participants. 144 prevalence of errors were not identified by the participants, 76.55% were concentrated on the items absence of the clamping device of the urine bag and urine volume in the bag higher than recommended; and 23.45% to fix the indwelling bladder catheter in an inappropriate region, incorrect storage of the collection bag on the floor and absence of personal protective equipment. Conclusion: It was proved that the health team was unaware of the frequency of daily hygiene of the urethral meatus, urine volume higher than that recommended in the urine bag and failure to observe the absence of a clamping device in the closed drainage system. Gaps that guide the planning and execution of the Continuing Health Education Service.